(untitled) (Filološke studije, 2019)
Human beings have, through their evolution, developed a universal ability to determine experiences, i.e. have begun coding and communicating with each other in symbols. Various explanations of the term ‘culture’ reflect different theories and criteria of evaluation, as well as different understandings of human activities. In this context, one of the products of culture is the establishment of towns. The city, in the words of the English linguist Michael Halliday, is the place of conversation. In an idealized sense, the speech community is a group of people (1) which is connected with some kind of social organization, (2) in which people talk with each other, and (3) where everyone speaks alike. The purpose of this paper is to show the linguistic expressions of the speakers within the Skopje language environment.